Naxalism - Agrawal, PK (New Delhi, 2010)
This book is a new approach to what and why of this vexed problem of uncontrolled violence by the Naxal rebels in state like Andhra Pradesh, Jharkhand, Chattisgarh, Bihar, Odisha, Madhya Pradesh etc.
Keywords: Naxalite movement